Declarative position of the BRICS on environmental and sustainable development issues - Astakhova Marina (BIO Web of Conferences)
In recent years environmental and sustainable development issues have grown in urgency and importance to the public. Policy makers, legislators and researchers actively address these problems. This research examines the declarative position of the BRICS on environmental and sustainable development issues. The relevance of the research is explained by the fact that current studies focus only on some environmental aspects of international treaties and national laws of the BRICS countries. The study of the declarative position of the BRICS based on the BRICS Summits Declarations adopted from 2011 to 2023. The norms of the Declarations are analyzed for the environmental and sustainable development provisions. As a result, it is concluded that the declarative position of the BRICS on environmental and sustainable development issues is a set of environmental and sustainable development provisions of the BRICS Summits Declarations containing opinions, intentions and, calls of the BRICS Heads of States. This study can contribute to a better understanding of the nature of the BRICS norms.